Frequencies of MNS Blood Group Antigens and Phenotypes in Southwestern Saudi Arabia - Halawani AJ (Dove Medical Press, 2021)
Amr J Halawani,1 Mahmoud M Habibullah,2,3 Gasim Dobie,2 Alaa Alhazmi,2,3 Farkad Bantun,4 Mohammed H Nahari,5 Ibrahim Dawmary,6 Hisham I Abu-Tawil6,7 1Department of Laboratory Medicine, Faculty of Applied Medical Sciences, Umm Al-Qura University, Makkah, Saudi Arabia; 2Department of Medical Laboratory Technology, Faculty of Applied Medical Sciences, Jazan University, Jazan, Saudi Arabia; 3SMIRES for Consultation in Specialized Medical Laboratories, Jazan University, Jazan, Saudi Arabia; 4Department of Microbiology, Faculty of Medicine, Umm Al-Qura University, Makkah, Saudi Arabia; 5Department of Clinical Laboratory Sciences, College of Applied Medical Sciences, Najran University, Najran, Saudi Arabia; 6Department of Laboratory and Blood Bank, Prince Mohammed bin Nasser Hospital, Ministry of Health, Jazan, Saudi Arabia; 7Department of Laboratory and Blood Bank, King Faisal Medical City for Southern Regions, Ministry of Health, Abha, Saudi ArabiaCorrespondence: Amr J Halawani Makkah, 24381 8156, Saudi ArabiaEmail ajjhalawani@uqu.edu.saPurpose: Knowledge of the prevalence of blood group antigens in a given population is important for the prevention of hemolytic reactions. The MNS blood group system (002) has four polymorphic antigens—M, N, S, and s. Anti-S and anti-s antibodies may result in immediate and delayed hemolytic transfusion reactions, and hemolytic disease of the fetus and newborn may occur. The present study investigated the frequencies of the main antigens and phenotypes of the MNS blood group system.Subjects and Methods: We randomly obtained 149 samples from anonymous Saudi blood donors living in Jazan Province. Serotyping was conducted using a gel card to investigate (M, N, S, and s) antigens and phenotypes.Results: The frequencies of MNS antigens were as follows: M = 89.26%, N = 51.67%, S = 61.07%, and s = 82.55%. Regarding the MNS phenotypes, nine phenotypes were observed in the study population. The most common phenotype was M+N–S+s+ (n = 36, 24.16%), in contrast to the least common phenotype M+N–S–s– (n = 1, 0.67%). The prevalence of the MNS phenotypes in the current study population was highly and significantly different from that in Europeans (P = 0.044) and African Americans (P = 0.000).Conclusion: In summary, this study reports the frequencies of the MNS antigens and phenotypes in Jazan Province, Saudi Arabia. The most common phenotype was M+N–S+s+, whereas the least observed phenotype was M+N–S–s–. The outcomes of this study may assist the blood banks in Jazan Province to establish an extended phenotyping protocol including the MNS antigens, in particular S and s antigens, to preclude any alloimmunization events.Keywords: MNS blood group, blood donors, transfusion, Saudi Arabia